1969
DOI: 10.1017/s0043174500030794
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Herbicides by Activated Carbon and other Adsorbents

Abstract: A root bioassay was used to compare the adsorption of herbicides by activated carbon with that of muck soil, bentonite clay, a cation exchange resin, and an anion exchange resin. The effectiveness of different adsorbents was determined by comparing the concentrations of herbicide required to give 50% root inhibition of the test plant. Of eight herbicides tested, six were more strongly adsorbed by activated carbon than by any of the other adsorbents. The relative amount of adsorption by activated carbon as meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Activated charcoal is a well documented herbicide safener (5,25) due to its large surface area and high adsorptive capacity (7,8). Lee (10) reported that 300 lb/acre activated charcoal in a 1‐inch band effectively safened six grass species when applied with atrazine and diuron.…”
Section: Safenersmentioning
confidence: 99%
“…Activated charcoal is a well documented herbicide safener (5,25) due to its large surface area and high adsorptive capacity (7,8). Lee (10) reported that 300 lb/acre activated charcoal in a 1‐inch band effectively safened six grass species when applied with atrazine and diuron.…”
Section: Safenersmentioning
confidence: 99%
“…This requires that seeded species be planted at the same time invasive weeds are being controlled (Sheley 2007). Activated carbon has a high adsorption capacity for a wide range of organic compounds, including many herbicides (Coffey and Warren 1969). Activated carbon has been used in croplands to deactivate herbicides in the immediate vicinity of seeded species, which allows concurrent planting and weed control.…”
Section: Introductionmentioning
confidence: 99%
“…The above conclusions on the soil relations of trifluralin are in apparent conformity with the general soil behaviour of many herbicides. However, the rate of inactivation of trifluralin by adsorbents appears to be particularly high (Coffey & Warren, 1969). It is noteworthy in this respect that although Newe Ya'ar clay contained about 2-5 times more organic matter and clay than Gilat sandy loam, the response to trifluraiin on these two soils difl'ered only slightly (Table I).…”
Section: Discussionmentioning
confidence: 92%
“…They found that organic matter was the soil component with the strongest reducing effect on phytotoxicity of trifiuralin and that clay, which had only a small effect when organic matter was removed, interacted synergistically in its presence. Among eight herbicides included in an inactivation study on adsorbents (Coffey & Warren, 1969), trifluralin showed the strongest adsorption on muck soil and on bentonite clay at very low concentration (0 01" ;) in the growth medium; the adsorption of trifluralin on activated carbon was about fifteen times stronger than on bentonite clay. Our results do not confirm the observation of Bardsley erai.…”
Section: Discussionmentioning
confidence: 98%